Chemical constituents and antioxidant activity of Cinnamomum microphyllum - Mohamad Ali, Nor Azah; Rahmani, Mawardi; Shaari, Khozirah; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd. Aspollah; Ali, Abdul Manaf; Ee, Gwendoline Cheng Lian (Universiti Putra Malaysia Press, 2010)
The extract of Cinnamomum microphyllum showed strong antioxidant activity when it was tested against auto-oxidation of linoleic acid, superoxide, and DPPH radical scavenging activity. Further detailed investigations of the plant constituents and bioactivity studies led to the isolation and identification of known compounds consisting of three lignans, a coumarin, an ester and β-sitosterol. The structures of the compounds were determined using detailed spectroscopic analysis. The lignans were found to possess a significant antioxidant activity when tested against the three assay systems.